Indicators of mineralocorticoid excess in the evaluation of primary aldosteronism - Balaş, Melania; Zosin, Ioana; Maser-Gluth, Christiane; Hermsen, Derik; Cupisti, Kenko; Schott, Matthias; Schinner, Sven; Knoefel, Wolfram T.; Scherbaum, Werner A.; Willenberg, Holger (Hypertension research, 2010)
It is sugges.ted to use the aldosterone-to-renin ratio (ARR) as a first test in the screening for primary aldosteronism (PA). However, many groups rather rely on the determination of urinary .tetrahydroaldosterone secretion; others calculate a ratio of urinary aldosterone to plasma renin activity. The aim of the present study was to evaluate the usefulness of different parameters of aldosterone excess in the case finding of PA. The study included 28 patients with PA and 33 subjects with essential hypertension. Clinical data, which included the hormonal parameters, serum aldosterone, plasma renin concentration, urinary free aldosterone and metabolites and serum and urinary electrolyte levels were analyzed. These indices of aldosterone excess, the ARR, serum sodium to urinary sodium to (serum potassium)2 to urinary potassium (SUSPPUP) ratio and combinations of these parameters were compared between the groups. Receiver-operating curve analysis revealed that the ARR multiplied by the SUSPPUP ratio (ARR × SUSPPUP) is the most reliable screening test, with a sensitivity of 92.3% and a specificity of 93.9% (cutoff point 199.2 (mmol l−1)−1). The combination of ARR × SUSPPUP ratio with urinary free aldosterone divided by the plasma renin concentration rendered a specificity of 100%. Less useful was the correction of urinary free aldosterone and its metabolites for sodium excretion. Although the ARR and urinary free aldosterone divided by renin are good tests in the screening for PA, the combination of ARR with SUSPPUP ratio is a better indicator of an aldosterone excess and aldosterone action in patients with ongoing antihypertensive medication. Antihypertensive drugs only marginally interfere with the SUSPPUP ratio, but they may influence the ARR, whereby the effects in PA patients seem to be negligible.
Gesehen am 24.11.2022